Tree Frog‐Inspired Structured Hydrogel Adhesive with Regulated Liquid. Issue 18 (23rd August 2021) - Meng, Fandong; Liu, Quan; Shi, Zhekun; Tan, Di; Yang, Baisong; Wang, Xin; Shi, Kui; Kappl, Michael; Lei, Yifeng; Liu, Sheng; Xue, Longjian
Abstract: The hexagonal epithelial cells covered with mucus are believed to be responsible for the superior adhesion ability of tree frogs under dry and wet conditions. In spite of good progress made in the past years, many questions about the mechanism of wet adhesion remain to be addressed. Here, a tree frog‐inspired wet adhesive, termed structured hydrogel adhesive, with poly(acrylamide)/poly(vinyl alcohol) hydrogel to mimic the hexagonal epithelial cells and glycerol–water mixture to mimic the mucus is reported. The combined analysis of adhesion force and work of adhesion reveals the major contribution of direct solid–solid contact in wet adhesion. The contributions of capillarity and viscosity of liquid are qualitatively decoupled by regulating the fluid components and the temperature. The study offers an excellent model system and a great opportunity to gain deep insight into wet adhesion of animals, like tree frogs, which may pave the way for the design of adhesives for wet environments. Abstract : Structured hydrogels are fabricated to mimic the adhesion system of tree frog toe pad. The combined analysis of adhesion force and work of adhesion reveals the major contribution of direct solid‐solid contact in wet adhesion. The contributions of capillarity and viscosity of liquid are decoupled by regulating the fluid components and the temperature, which deepens insight into wet adhesion.